3D culture broadly regulates tumor cell hypoxia response and angiogenesis via pro-inflammatory pathways. (July 2015) - DelNero, Peter; Lane, Maureen; Verbridge, Scott S.; Kwee, Brian; Kermani, Pouneh; Hempstead, Barbara; Stroock, Abraham; Fischbach, Claudia
Abstract: Oxygen status and tissue dimensionality are critical determinants of tumor angiogenesis, a hallmark of cancer and an enduring target for therapeutic intervention. However, it is unclear how these microenvironmental conditions interact to promote neovascularization, due in part to a lack of comprehensive, unbiased data sets describing tumor cell gene expression as a function of oxygen levels within three-dimensional (3D) culture. Here, we utilized alginate-based, oxygen-controlled 3D tumor models to study the interdependence of culture context and the hypoxia response. Microarray gene expression analysis of tumor cells cultured in 2D versus 3D under ambient or hypoxic conditions revealed striking interdependence between culture dimensionality and hypoxia response, which was mediated in part by pro-inflammatory signaling pathways. In particular, interleukin-8 (IL-8) emerged as a major player in the microenvironmental regulation of the hypoxia program. Notably, this interaction between dimensionality and oxygen status via IL-8 increased angiogenic sprouting in a 3D endothelial invasion assay. Taken together, our data suggest that pro-inflammatory pathways are critical regulators of tumor hypoxia response within 3D environments that ultimately impact tumor angiogenesis, potentially providing important therapeutic targets. Furthermore, these results highlight the importance of pathologically relevant tissue culture models to study the complex physical and chemical processes by which the cancer microenvironment mediates new vessel formation.